1992
DOI: 10.1055/s-2006-961532
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gomisin A (TJN-101) on Liver Regeneration

Abstract: We studied the effect of TJN-101, a lignan component of Schisandra fruits (Schisandrae fructus), on liver regeneration after partial hepatectomy. TJN-101 was given orally to male Wistar rats 30 min before partial hepatectomy. The mitotic index and the level of DNA synthesis increased after partial hepatectomy and their increase was significantly enhanced by TJN-101. Ornithine decarboxylase (ODC) activity increased in the early stages of liver regeneration and it was also significantly enhanced by TJN-101. Besi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 6 publications
0
25
0
Order By: Relevance
“…The aforementioned ligands contribute to the hepatic regeneration process via the induction of mRNA transcription for hepatocyte growth factor, as well as the stimulation of hepatocyte proliferation and increased blood flow to the liver. Additionally, in an effort to improve regenerative capacity via reduced glutation and the synthesis of hepatic glucogen, the addition of these lignans induces increases in the levels of mitochondrial hepatic glutation and mitochondrial reductase glutation activity (31,32). However, relatively few functional studies have been conducted to investigate in detail whether the novel lignans isolated from S. chinensis influence cell death of the hepatocellular carcinoma cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned ligands contribute to the hepatic regeneration process via the induction of mRNA transcription for hepatocyte growth factor, as well as the stimulation of hepatocyte proliferation and increased blood flow to the liver. Additionally, in an effort to improve regenerative capacity via reduced glutation and the synthesis of hepatic glucogen, the addition of these lignans induces increases in the levels of mitochondrial hepatic glutation and mitochondrial reductase glutation activity (31,32). However, relatively few functional studies have been conducted to investigate in detail whether the novel lignans isolated from S. chinensis influence cell death of the hepatocellular carcinoma cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…ir spectra were recorded on an aaTi Mattson Genesis Series FTir. nMr spectra ( 1 H, 13 c) were recorded in cdcl 3 on a Varian inova 500 Spectrometer operating at 500 MHz for 1 H and 125 MHz for 13 c, running gradients and using residual solvent peaks as internal references. High-resolution mass spectra were recorded on a Bruker Bioapex FT Mass Spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…regarding the third category, hepatic stabilization, previous studies have shown that these compounds contribute to the hepatic regeneration process through the induction of hepatocyte growth factor mrna transcription, the stimulation of hepatocyte proliferation, and increased blood flow to the liver. in addition, in order to improve regenerative capacity through reduced glutation and the synthesis of hepatic glucogen, these lignans induce an increase in the levels of mitochondrial hepatic glutation and the activity of mitochondrial reductase glutation (12,13). However, few functional studies have been conducted to fully investigate whether the lignans isolated from Schisandra chinensis have an effect on cell death in hepatic carcinoma in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Current scientific findings suggest that lignans of Schisandra chinensis, the active ingredients can stimulate liver regeneration, prevent liver injuries and inhibit hepatocarcinogenesis as well as lipid peroxidation in rats (Hikino et al, 1984;Kubo et al, 1992). Also, other pharmacological effects such as lowering the serum glutamate-pyruvate transaminase level, inhibiting platelet aggregation, and anti-oxidative, calcium antagonism, anti-tumor and anti-HIV (human immunodeficiency virus) effects of Schisandra chinensis can also be attributed to its lignan constituents, particularly the 14 dibenzocyclooctadiene-type lignans (Lu and Chen, 2009).…”
Section: Schisandra Chinensis (Wu Wei Zi)mentioning
confidence: 99%